(untitled) - Jason Fried; David Heinemeier Hansson (London Vermilion, 2020)
From the founders of the trailblazing software company 37signals, here is a different kind of business book - one that explores a new reality. Today, anyone can be in business. Tools that used to be out of reach are now easily accessible. Technology that cost thousands is now just a few pounds or even free. Stuff that was impossible just a few years ago is now simple. That means anyone can start a business. And you can do it without working miserable 80-hour weeks or depleting your life savings. You can start it on the side while your day job provides all the cash flow you need. Forget about business plans, meetings, office space - you don't need them. With its straightforward language and easy-is-better approach, Rework is the perfect playbook for anyone who's ever dreamed of doing it on their own. Hardcore entrepreneurs, small-business owners, people stuck in day jobs who want to get out, and artists who don't want to starve anymore will all find valuable inspiration and guidance in these pages. It's time to rework work.
Keywords: Business; Entrepreneurship; Leadership; Nonfiction; Productivity; Self Help